Biography of Jack Holland (1926-2014): Chert expert - William Engelbrecht; Lisa Marie Anselmi (Journal of Lithic Studies, 2015)
Jack was born and grew up in Lock Haven Pennsylvania, the son of William G. Holland and Florence (Davies) Holland. He had an older brother, William and a younger brother, Donald. Jack spent much of his boyhood roaming the surrounding flood plains of the West Branch of the Susquehanna River looking for arrowheads. As Jack recalled, his parents gave him a great deal of freedom, just asking that he be home in time for dinner. Dr. T. B. Stewart, a Lock Haven dentist, encouraged Jack’s early archaeological interest, helping him to identify specimens. Dr. Stewart had an extensive archaeological collection and had worked with Donald Cadzow, Pennsylvania’s State Archaeologist (1929-1939). Dr. Stewart was also one of the founders of the Society for Pennsylvania Archaeology, an organization with which Jack would later become involved and that bestowed their J. Alden Mason Award on him as a professional who encouraged society members in the “proper pursuit of archaeology.”